Research on Transient Electromagnetic Fast Imaging in Water Rich Area of Mine Goaf - YUAN Yongbang (Meikuang Anquan, 2020)
To quickly and accurately detect the goaf rich water area in front of the coal mine roadway, MATLAB program is used to convert the secondary field induced voltage Vz(t) obtained by TEM into vertical field Hz(t)to calculate all-time apparent resistivity quickly. The apparent depth is calculated according to the “smoke circle” theory to form a pseudo section diagram of the apparent resistivity, so as to realize the fast imaging of the apparent resistivity in the detection process. The effect is observed through the forward modeling of multi-layer dielectric geo-electric model and the detection of driving face. The calculation of the model and the application of an example show that the conversion of the induced voltage to the vertical magnetic field has the advantages of high accuracy and high speed in calculating all-time apparent resistivity; the fast apparent resistivity imaging of underground site can realize the preliminary interpretation of the water rich anomaly, and timely retest of the anomaly on site is conducive to improving the accuracy of detection.